Islamic Law and the Management of Qurban Savings: A Case Study of Darul Ihsan Mosque, Tuban - Moh. Khoirul Anwar; Ahmad Musadad; Moh. Karim; Fajar Fajar; M. Faiz Nashrullah (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The management of Qurban savings by the Darul Ihsan Mosque in Banjarworo Village, Bangilan District, Tuban Regency, has garnered attention. This is primarily because it originates from a non-financial, socially-oriented institution dedicated to facilitating Qurban participation for underprivileged communities. This study aimed to investigate the operational mechanisms of this Qurban savings program and assess its compliance with Islamic law. The research employed a qualitative approach utilizing field data (field research) with a descriptive-analytical nature, complemented by a normative-empirical perspective. Data collection involved observation, interviews, and documentation. The collected data were then analyzed using the Miles and Huberman model. The findings indicate that the practices of this Qurban savings program align with the principles of wadi>‘ah yad al-ama>nah, Fatwa DSN-MUI Number: 02/DSN-MUI/IV/2000 concerning savings, and the regulations outlined in KHES (Compilation of Islamic Economic Law). However, the study identified instances of default by participants due to delayed payments. Despite these challenges, the program genuinely reflects the objectives of maqa>s}id al-shari>‘ah, particularly concerning the preservation of wealth (h}ifz} al-ma>l) and the preservation of religion (h}ifz} al-di>n). Furthermore, it provides substantial social and spiritual benefits to the community.